Sentiment prevalence on jihad, caliphate, and bid’ah among Indonesian students: focusing on moderate-radical Muslim group tension - Hanafi, Yusuf; Arifianto, Muhammad Lukman; Saefi, Muhammad; Mahliatussikah, Hanik; Anam, Faris Khoirul; Hassan, Abd Rauf; Hidayatullah, Muhammad Fahmi (Taylor and Francis, 2022)
In reality, many students misunderstand several Islamic religious terms that come from Arabic; regarding jihad, caliphate, and bid’ah. This study used qualitative and quantitative data collection methods to investigate students’ perspectives on these terms. We collected data through a questionnaire on 122 Muslim students at the university who were suspected of being exposed to radicalism. After examining student responses, our examination led to mapping “positive,” “moderate,” and “negative” sentiments. The results revealed that few students achieved a positive category. Students expressed their attitudes, beliefs, and evaluations that the term Islam was abused and associated with violence, enforcement of the caliphate, and accusations of bid’ah against different groups. Analysis of data on student comments revealed that students’ meaning of terms tended to be influenced by the definition of radical Muslim groups. These findings indicate that radical groups can influence the way students interpret a term and create negative sentiments. Through this research, we suggest that “an indicator of moderate-radical Muslim group tension,” in the context of this study, between Nahdlatul Ulama and Muhammadiyah versus Hizbut Tahrir Indonesia, can be used as material for deradicalisation policies for campuses in Indonesian.